PENINGKATAN HASIL BELAJAR PKN DENGAN MENERAPKAN LITERASI TERBIMBING PADA PESERTA DIDIK KELAS VI SDN 04 SUNGAI TALANG TAHUN PELAJARAN 2018/2019 - ,, Erna (RC-INSTITUT, 2019)
The background of his research is the students? saturation and difficulties in understanding the material of Pendidikan Kewarganegaraan (PKn). This problem resulted that student learning outcomes in Civics lessons are low. The purpose of this study was to describe the improvement in PKn learning outcomes by applying guided literacy for class VI students of SDN 04 Sungai Talang in the 2018/2019 academic year. This type of research is Classroom Action Research (CAR), which consists of planning, action, observation, and reflection. The subjects of this study were sixth grade students of SDN 04 Sungai Talang. The results of each cycle indicate an increasing  in learning outcomes. In the first cycle the percentage of students who achieved the Minimum achievement criterion (KKM)  was 75%, so it was continued to cycle II. The percentage of completeness of student learning outcomes in the second cycle was 95%. The conclusion in this study was that there was an increasing of the  students? learning outcomes in PKn by applying guided literacy for class VI students of SDN 04 Sungai Talang in the 2018/2019 academic year.